Highly Prevalent Multidrug-Resistant Salmonella From Chicken and Pork Meat at Retail Markets in Guangdong, China - Zhang, Lina; Fu, Ying; Xiong, Zhiying; Ma, Yeben; Wei, Yihuan; Qu, Xiaoyun; Zhang, Hongxia; Zhang, Jianmin; Liao, Ming (Frontiers in Microbiology, 2018)
This study aimed to investigate prevalence, serotype distribution, antimicrobial resistance (AMR) and to characterize extended spectrum β-lactamases (ESBLs) producing Salmonella isolates from chicken and pork meats at retail markets in Guangdong province, China. A total of 903 retail meat samples (including 475 chicken and 428 pork meats) were obtained from six cities (Guangzhou, Shenzhen, Heyuan, Shaoguan, Foshan and Yunfu) of Guangdong province collected between May 2016 and April 2017. High levels of Salmonella contamination were detected in chicken (302/475, 63.6%) and pork (313/428, 73.1%). Thirty-eight serotypes were identified in 615 Salmonella, and the serotypes vary greatly between chicken and pork samples. Agona (55/302, 18.2%), Corvallis (45/302, 14.9%), Kentucky (38/302, 12.6%), Mbandaka (32/302, 10.6%) was the dominant serotypes in chicken samples. However, Typhimurium (78/313, 24.9%), Rissen (67/313, 24.1%), Derby (66/313, 21.1%) and London (48, 15.3%) was the most common in pork samples. High antibiotic resistance rates were found in sulfisoxazole (468/615, 76.1%), tetracycline (463/615, 75.3%), ampicillin (295/615, 48.0%), ofloxacin (275/615, 44.7%). Notably, the results of antimicrobial susceptibility test found the resistant rate of polymyxin B (12/615, 2.0%) and imipenem (3/615, 0.5%). Multidrug-resistance (MDR) was detected in chickens (245/302, 81.1%) and porks (229/313, 73.2%). Resistant rate of Salmonella in different serotypes vary widely. Especially, isolates such as S. Typhimurium, S. Agona, S. Corvallis and S. kentucky exhibited highly resistant to antibiotics. The MDR rate of Salmonella of chickens is significantly higher than that of porks (P<0.05). Twenty-one Salmonella isolates were identified as ESBLs-producing, covered 6 Salmonella serotypes and displayed different PFGE genotypes. BlaOXA-1 was the dominant ESBLs gene (9/21, 42.9%), followed by blaCTX-M-55 (5/21, 23.8%). This study indicated that Salmonella was widespread in chicken and pork at retail markets in Guangdong province and has high multidrug-resistance, especially multidrug-resistant serotype Salmonella. So, it is important to should focus on Salmonella serotype and strengthend the long-term monitoring of MDR serotype Salmonella in animal-derived foods.